The Relationship Between School Origin, Gender, Region and UMPTKIN Scores in IAIN Kendari and UINSA Surabaya - Huriyah, Lilik; Kusaeri, Kusaeri; Yusuf, Ahmad; Asmiyah, Siti; Rohman, Abid (KnE Social Sciences, 2022)
This research aimed to measure the relationship of school origin, gender and region with the UMPTKIN scores in IAIN Kendari and UINSA Surabaya. This was quantitative research. Cluster sampling was used to recruit 100 test-takers in IAIN Kendari and 86 in UINSA Surabaya. Data analysis involved Kendall’s Tau b correlation test. The results showed a significant relationship between gender and score in IAIN Kendari (p = 0.006) and between school origin and score in UINSA (p = 0.014). The level of correlation between school origin, gender and region with UMPTKIN score was low at both universities. The findings confirmed existing theories on the relationship of school, gender and region with learning scores. Keywords: types of school origin, gender, region, enrollment examination for state Islamic religious colleges